Description of twelve new species of the genus Ripeacma Moriuti, Saito & Lewvanich (Lepidoptera: Autostichidae) from China - Xu, Zhixin; Wang, Shuxia (Zootaxa, 2022)
Twelve new species of the genus Ripeacma Moriuti, Saito & Lewvanich, 1985 are described: R. anisopenis sp. nov., R. apicilispina sp. nov., R. bihamatilis sp. nov., R. bitriangulata sp. nov., R. dissectaedeaga sp. nov., R. magnimaculata sp. nov., R. stigmosa sp. nov., R. acerba sp. nov., R. ellipsoidea sp. nov., R. hamatispina sp. nov., R. mediprocessa sp. nov. and R. trilobata sp. nov.; R. chandratati Moriuti, Saito et Lewvanich, 1985 is newly recorded for the Chinese fauna. Images of adults and genitalia of the new species are provided.